Retrieving the American past : (Simon & Schuster Custom Pub., 1996)
Contents: Table of Contents: The Rise of big Business and the Persistence of Small Business in American Industry, 1850-1920. The Industrial City. The Age if Industrial Violence. The Emergence of the Modern Day Labor Movement. The Grueling Battle for Women Sufferage. Clash of Cultures in the 1910's and 1920's. Anti-Communism at home. American Life in the 1950's. The Environmental Movement. Why did the U.S. lose the Vietnam War?